Optimization Extraction of Xylocarpus granatum Stem as Antioxidant and Antiglycation - Eka Winarni Sapitri; Irmanida Batubara; Utami Dyah Syafitri (HAYATI Journal of Biosciences, 2019)
Xylocarpus granatum is an Indonesian plant that has bioactives content of phenols and high antioxidant activity on it. The aim of this research was to determine the optimum condition maceration for Xylocarpus granatum stem as antioxidant and antiglycation. The optimum conditions of maceration were effected by the extraction variables (concentration, sample/solvent ratio, extraction time) were evaluated using surface response method. The optimum condition was determined from the recovery of the respons. The optimum condition of maceration is predicted to be achieved when the solvent concentration is 52.25%, the extraction time is 15.92 hours, sample/solvent ratio is 1 g/9 ml with the response (yield, total phenol content, flavonoid, inhibition for 2,2’-diphenylpicryl hydrazyl, capacity of 2,2’-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), and inhibition antiglycation were 12.81%, 1.95 mg of gallic acid/g extract, 62.33 μg quercetin/g extract, 41.11%, 0.71 TEAC, and 112.33%, respectively). Optimization extraction conditions shows that the extraction variables have significant effect on respons so it can reduce the extraction time, economic, and produce high bioactivite constituens.